2010
DOI: 10.1099/vir.0.016717-0
|View full text |Cite
|
Sign up to set email alerts
|

Murine norovirus-1 cell entry is mediated through a non-clathrin-, non-caveolae-, dynamin- and cholesterol-dependent pathway

Abstract: For many viruses, endocytosis and exposure to the low pH within acidic endosomes is essential for infection. It has previously been reported that feline calicivirus uses clathrin-mediated endocytosis for entry into mammalian cells. Here, we report that infection of RAW264.7 macrophages by the closely related murine norovirus-1 (MNV-1) does not require the clathrin pathway, as infection was not inhibited by expression of dominant-negative Eps15 or by knockdown of the adaptin-2 complex. Further, infection was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 51 publications
2
57
1
1
Order By: Relevance
“…MNV-1 and S99 binding to murine macrophages is dependent on terminal sialic acid residues of the ganglioside GD1a, N-linked, or O-linked glycoproteins, while CR3 binding requires only N-linked glycoproteins (21,22). Although multiple studies have elucidated aspects of the multistep process by which MNV enters permissive macrophages (21)(22)(23)(24)(25), how the virus crosses the intestinal epithelial barrier to reach susceptible macrophages and dendritic cells in the first place is unknown.…”
mentioning
confidence: 99%
“…MNV-1 and S99 binding to murine macrophages is dependent on terminal sialic acid residues of the ganglioside GD1a, N-linked, or O-linked glycoproteins, while CR3 binding requires only N-linked glycoproteins (21,22). Although multiple studies have elucidated aspects of the multistep process by which MNV enters permissive macrophages (21)(22)(23)(24)(25), how the virus crosses the intestinal epithelial barrier to reach susceptible macrophages and dendritic cells in the first place is unknown.…”
mentioning
confidence: 99%
“…MNV has also been isolated from wild mice, confirming its widespread distribution (59). Studies with MNV have begun to probe various aspects of the norovirus replication cycle, including entry mechanisms and attachment factors (24,48,49,67), viral protein function (8,19,30,43,64,66), determinants of virulence (7), and host immune responses (14, 15, 42); however, our understanding of the molecular mechanisms of norovirus genome translation and replication lags far behind that for other RNA viruses.MNV is a positive-sense single-stranded RNA virus with a genome of approximately 7.4 kb covalently attached to a viral genome-linked protein (VPg) at the 5= end and polyadenylated at the 3= end (33). The 5= and 3= untranslated regions (UTRs) are extremely short, 5 and 78 nucleotides (nt), respectively, for MNV-1 (33).…”
mentioning
confidence: 99%
“…8 Many viruses, such as the influenza, Sendai, and echoviruses, were also found to infect cells utilizing non-clathrin-and non-caveolaemediated pathways for transport to the golgi apparatus and, subsequently, to the endoplasmic reticulum. 9,10 Previous research has reported that the mode of complex internalization might affect not only the intracellular processing kinetics but also the transfection efficiency. 11 Thus, we studied the intracellular processing of polyplexes and liposomes internalized by different endocytosis pathways We explored the colocalization of the two types of fluorescence using laser scanning confocal microscopy, which showed yellow particles in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%